Metabolic regulation of T cells in the tumor microenvironment by nutrient availability and diet. (February 2021) - Zhao, Steven; Peralta, Ronal M.; Avina-Ochoa, Natalia; Delgoffe, Greg M.; Kaech, Susan M.
Abstract: Recent advances in immunotherapies such as immune checkpoint blockade (ICB) and chimeric antigen receptor T cells (CAR-T) for the treatment of cancer have generated excitement over their ability to yield durable, and potentially curative, responses in a multitude of cancers. These findings have established that the immune system is capable of eliminating tumors and led us to a better, albeit still incomplete, understanding of the mechanisms by which tumors interact with and evade destruction by the immune system. Given the central role of T cells in immunotherapy, elucidating the cell intrinsic and extrinsic factors that govern T cell function in tumors will facilitate the development of immunotherapies that establish durable responses in a greater number of patients. One such factor is metabolism, a set of fundamental cellular processes that not only sustains cell survival and proliferation, but also serves as a means for cells to interpret their local environment. Nutrient sensing is critical for T cells that must infiltrate into a metabolically challenging tumor microenvironment and expand under these harsh conditions to eliminate cancerous cells. Here we introduce T cell exhaustion with respect to cellular metabolism, followed by a discussion of nutrient availability at the tumor and organismal level in relation to T cell metabolism and function to provide rationale for the study and targeting of metabolism in anti-tumor immune responses.